Rotation of male genitalia in various species of phlebotomine sandfly - Votýpka, J; Pavlasova, M; Volfova, V; Volf, P (Medical and veterinary entomology, 2015)
Phlebotomine sandflies, vectors of Leishmania (Kinetoplastida: Trypanosomatidae) parasites that affect millions of people worldwide, breed in terrestrial biotopes. As immature stages are rarely accessible, the detection of their natural breeding sites is primarily based on findings of juvenile males with unrotated external genitalia. In males, permanent 180° rotation on the longitudinal body axis occurs soon after eclosion; however, no study has as yet addressed this aspect in detail. The present study describes the timing and duration of the rotation of male external genitalia in eight highly medically important sandfly species belonging to the genera Sergentomyia, Lutzomyia and Phlebotomus (all: Diptera: Psychodidae), kept under controlled laboratory conditions. The average duration of rotation was species-specific and varied from 12 h in Sergentomyia schwetzi to 33 h in Phlebotomus sergenti. Significant differences in rotation times were found among species, even between two closely related species of the subgenus Larroussius, Phlebotomus orientalis and Phlebotomus tobbi. The rotation of genitalia in all three studied genera was randomly oriented and similar numbers of clockwise and counter-clockwise events were observed. The study also addresses the effects of some external factors. In all species studied, rotation was not affected by the time of day of eclosion. Similarly, no differences in total rotation time were found between Phlebotomus papatasi males maintained at 25 and 20 °C, respectively. The present findings will assist in the search for natural breeding sites and in studies aimed at elucidating strategies for integrated sandfly and leishmaniasis control.
Keywords: biology and behaviour; Genitalia, Male; Sergentomyia; Phlebotomus; mužské pohlavní orgány; Animals; Pupa; mužské pohlaví; Psychodidae; Male; leishmaniasis; zvířata; Lutzomyia; kukla; laboratory colony